International Development Policy: Religion and Development - Carbonnier, G.; Carbonnier, G. (International Development Policy, 2013)
The rise of fundamentalist movements in major religions has forced decision-makers, development organizations and academics to turn their attention to its meaning for development. Global scholars and practitioners examine these issues and fundamentally question the secular-religious dichotomy in development discourse and practice.